Dynamic Gait Analysis in Paediatric Flatfeet: Unveiling Biomechanical Insights for Diagnosis and Treatment - Böhm, Harald; Stebbins, Julie; Kothari, Alpesh; Dussa, Ugandhar Chakravarthy (Children, 2024)
Background: Flatfeet in children are common, causing concern for parents due to potential symptoms. Technological advances, like 3D foot kinematic analysis, have revolutionized assessment. This review examined 3D assessments in paediatric idiopathic flexible flat feet (FFF). Methods: Searches focused on paediatric idiopathic FFF in PubMed, Web of Science, and SCOPUS. Inclusion criteria required 3D kinematic and/or kinetic analysis during posture or locomotion, excluding non-idiopathic cases, adult feet, and studies solely on pedobarography or radiographs. Results: Twenty-four studies met the criteria. Kinematic and kinetic differences between FFF and typical feet during gait were outlined, with frontal plane deviations like hindfoot eversion and forefoot supination, alongside decreased second peak vertical GRF. Dynamic foot classification surpassed static assessments, revealing varied movement patterns within FFF. Associations between gait characteristics and clinical measures like pain symptoms and quality of life were explored. Interventions varied, with orthoses reducing ankle eversion and knee and hip abductor moments during gait, while arthroereisis normalized calcaneal alignment and hindfoot eversion. Conclusions: This review synthesises research on 3D kinematics and kinetics in paediatric idiopathic FFF, offering insights for intervention strategies and further research.
CRIS-Team Scopus Importer:2024-05-31
Keywords: flexible flatfoot; kinematics; kinetics; multi segment foot model; pes planus; walking

Management of Severe Equinovalgus in Patients With Cerebral Palsy by Naviculectomy in Combination With Midfoot Arthrodesis - Dussa, Ugandhar Chakravarthy; Doederlein, Leonhard; Forst, Raimund; Boehm, H.; Fujak, Albert (Foot & Ankle International, 2017)
BACKGROUND: Equinovalgus deformity is the second most common deformity in cerebral palsy and may be flexible or rigid. Several operative methods from joint sparing to arthrodesis have been described with varying success rates. The aim of this study was to investigate the effectiveness of naviculectomy in combination with midfoot arthrodesis (talo-cuneiform and calcaneocuboid arthrodesis) in the correction of a rigid equinovalgus foot deformity in cerebral palsy. METHODS: Forty-eight rigid equinovalgus feet were operated upon in 30 patients from 2008 to 2013. Of these, 44 feet in 26 patients with cerebral palsy (Gross Motor Function Classification System III, IV, or V) with follow-up of more than 2 years were included in the study. The mean age at surgery was 18.1 years. The outcomes were measured objectively using radiographic angles and subjectively using 5 questions to be answered by the caregiver. The feet were then graded into excellent, good, fair, and poor. The mean follow-up was 5.0 ± 1.7 years. RESULTS: Excellent to good results were obtained in 81% of the feet. Both objective and subjective outcomes improved significantly postoperatively ( P < .001). Three feet in 2 patients were graded as poor and underwent a revision operation for pain and recurrence. CONCLUSIONS: Naviculectomy in combination with midfoot arthrodesis enabled a good 3-dimensional correction of the forefoot. However, the procedure did not necessarily correct the fixed subtalar joint deformity. Several additional bony and soft-tissue procedures were necessary to achieve a complete correction in these difficult feet. LEVEL OF EVIDENCE: Level IV, retrospective case series.
EVALuna2:33710

Status of surface electromyography assessment as part of clinical gait analysis in the management of patients with cerebral palsy – Outcomes of a Delphi process - Reisig, Robert; Alexander, Nathalie; Armand, Stéphane; Barton, Gabor J.; Böhm, Harald; Boulay, Christophe; Brunner, Reinald; Castagna, Anna; Davoudi, Mehrdad; Desailly, Eric; Desloovere, Kaat; Dussa, Ugandhar Chakravarthy; et al. (Gait & Posture, 2025)
Background: The assessment of gait disorders in patients with neuromotor conditions, such as cerebral palsy (CP), has been a focus of clinical and research attention, with electromyography (EMG) offering a nuanced understanding of neurological and neuromuscular disorders. However, the interpretation of EMG data in the context of gait analysis remains challenging due to the complexity of neuromotor dynamics and variability in assessment methodologies. Research question: To which consensus can we get in a group of experts in the fields of neurological and neuromuscular disorders, biomechanics, and clinical gait analysis to establish standardized protocols and a common language for the measurement and analysis of EMG data in gait disorders, particularly in people living with CP? Methods: A three-round Delphi process was conducted from February to September 2023 to gather opinions of 53 experts on the use of surface EMG data during gait in the context of CP. The surveys were conducted using the tool 'SoSci Survey' with a focus on free-text answers. Results: The experts agreed on the usefulness of EMG data, but a consensus on specific clinical decisions involving EMG could not be reached. Additionally, the study provides a terminological framework for EMG evaluation during gait and a comprehensive list of practical problems and solutions, when evaluating EMG data. The study indicates that, despite a general community consensus on the ideal approaches to data processing and evaluation, these methods are not commonly implemented in a standardized manner. Both raw and enveloped data are widely used in clinical routines, however, the protocol for generating normative data lacks consistency across gait laboratories. Significance: The study suggests that while there may be differences in the way EMG data is analyzed, there is a shared understanding of the key features that are relevant for gait analysis.
CRIS-Team Scopus Importer:2025-02-17
Keywords: Cerebral Palsy; Consensus; Delphi; Dynamic EMG; Muscle activity